Castor oil polyurethane containing silica nanoparticles as filling material of bone defect in rats - Nacer,Renato Silva (2012)
PURPOSE: To evaluate the biologic behavior of the castor polymer containing silica nanoparticles as a bone substitute in diafisary defect. METHODS: Twenty seven male rattus norvegicus albinus wistar lineage were submitted to bone defect filled with castor oil polymer. Three experimental groups had been formed with nine animals each: (1) castor oil polymer containing only calcium carbonate; (2) castor oil polymer with calcium carbonate and doped with 5% of silica nanoparticles; (3) castor polymer with calcium carbonate doped with 10% of silica nanoparticles; 3 animals of each group were submitted to euthanasia 15, 30 and 60 days after experimental procedure, and their femurs were removed to histological evaluation. RESULTS: there was bone growth in all the studied groups, with a greater tendency of growth in the group 1. After 30 days all the groups presented similar results. After 60 days a greater amount of fibroblasts, osteoblasts, osteocytes and osteoclasts in group 3 was observed, with integrated activity of 3 kinds of cells involved in the bone activation-reabsorption-formation. CONCLUSIONS: The castor polymer associated to the silica nanoparticles is biocompatible and allows osteoconduction. The presence of osteoprogenitors cells suggests silica osteoinduction capacity.